RAMP - risk analysis and management for projects : a strategic framework for managing project risk and its fiancial implications - Institute and Faculty of Actuaries (Great Britain); Institution of Civil Engineers (Great Britain) (London : ICE Publishing, 2014)
Describing the process for analysing and responding to risks which can affect the overall success of projects, this text meets a more rigorous approach to risk management which can be used in a variety of contexts
Previous edition : 2005
Includes bibliographical references and index
Print version record
UCLA Library - CDL shared resource.
NEW
Keywords: Capital investments; Risk management